THE COMBINED EFFECT OF BIO-STIMULANTS ON THE FLOWER GROWTH, YIELD, AND ESSENTIAL OIL CHARACTERISTIC OF CUMIN - Mahdi s. J.; S. B. I. Mustafa (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was conducted during two winter seasons 2020-2019 and 2021-2020 at the College of Agricultural Engineering Sciences-University of Baghdad (Al-Jadriya). To improve the efficiency and productivity of the flower growth, yield, and essential oil characteristic of cumin (Cuminum cyminum L.). The experiment included two-factors, the first with four levels of bio-fertilizers (without vaccination, Pseudomonas fluorescens, Azospirillum brasilense, and mixture between vaccination), while the second with a combination of five levels that included two treatments (15 and 30 ml L-1) for each of coconut endosperm fluid and tryptophan with one metering treatment for both (sprayed with distilled water). Randomized complete block design (RCBD) was used in a spilt-plot design with three replications. The results showed that all studied traits were affected by the study factors for both seasons, as the plants treated with the spray combination (30 ml L-1 each) with mixture between vaccination gave superiority in most of the within, and the interaction effect between the study factors was significant compared to the plants uninoculated and unsprayed for both seasons.